2014
DOI: 10.1021/ml500220a
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Ligand Cocrystal Structures: We Can Do Better

Abstract: There is a large body of evidence that many protein−ligand cocrystal structures contain poorly refined ligand geometries. These errors result in bound structures that have nonideal bond lengths and angles, are strained, contain improbable conformations, and have bad protein−ligand contacts. Many of these problems can be greatly reduced with better refinement models. KEYWORDS: Protein−ligand cocrystal, structure-induced fit, structure-based design, structure refinement, bound ligand strain T he ability to accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…More recently, another study reported a worrying situation affecting ring conformation , using N-glycan-forming d-pyranosides as an example, although the results clearly extend not only to all pyranose sugars but to every ligand with a saturated six-membered ring. In general, the software tools that deal admirably with proteins (Murshudov et al, 2011;Adams et al, 2011;Emsley et al, 2010;Blanc et al, 2004;Brü nger et al, 1998), and nucleic acids to some extent, appear to have problems handling ligands at lower resolution (Reynolds, 2014;Liebeschuetz et al, 2012;Perola & Charifson, 2004), with thousands of structures showing angle and torsional strains that cannot be supported unequivocally by the experimental data. Pyranosides, and indeed all saturated cyclic compounds, might not necessarily show such strains, but can be spuriously locked into secondary energy minima (typically boat conformations) that may only show transannular strain after rounds of model refinement against low-resolution data.…”
Section: Cinderella's Coach May Not Be Ready Yetmentioning
confidence: 99%
“…More recently, another study reported a worrying situation affecting ring conformation , using N-glycan-forming d-pyranosides as an example, although the results clearly extend not only to all pyranose sugars but to every ligand with a saturated six-membered ring. In general, the software tools that deal admirably with proteins (Murshudov et al, 2011;Adams et al, 2011;Emsley et al, 2010;Blanc et al, 2004;Brü nger et al, 1998), and nucleic acids to some extent, appear to have problems handling ligands at lower resolution (Reynolds, 2014;Liebeschuetz et al, 2012;Perola & Charifson, 2004), with thousands of structures showing angle and torsional strains that cannot be supported unequivocally by the experimental data. Pyranosides, and indeed all saturated cyclic compounds, might not necessarily show such strains, but can be spuriously locked into secondary energy minima (typically boat conformations) that may only show transannular strain after rounds of model refinement against low-resolution data.…”
Section: Cinderella's Coach May Not Be Ready Yetmentioning
confidence: 99%
“…The Engh and Huber equilibrium bond lengths and angles Huber, 1991, 2001) were used for several decades, but have been superseded by conformation dependent restraint libraries Tronrud et al, 2010) for the backbone atoms. Generating restraints for small molecules, however, is significantly harder, due to the vastly increased chemical space that they can occupy and limited available data; in conjunction with the observation that ligand densities are typically less resolved compared to their surroundings, either due to a superposition of states, partial occupancy, increased mobility, or any combination of these, this has led to a number of critical publications addressing the quality of ligands deposited in the PDB (Deller and Rupp, 2015;Liebeschuetz et al, 2012;Peach et al, 2017;Reynolds, 2014, Sitzmann et al, 2012. The wwPDB formed a working group to define proper ligand validation protocols to combat these issues, with several recommendations already being implemented .…”
Section: Introductionmentioning
confidence: 99%
“…20 Attempts have thus been made by us 21,22 and others 23 to delineate the structural features of ligand-dependent CB1R activation using computational prediction methods, albeit with underlying assumptions regarding the states of apo- and holo-CB1R in situ . This laboratory has also utilized nuclear magnetic resonance spectroscopy (NMR) to characterize experimentally the structure and dynamics of discrete CB1R transmembrane helix (TMH) domains.…”
mentioning
confidence: 99%